2017
DOI: 10.2337/db17-0414
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Metabolic Remodeling During Type 2 Diabetes Remission After Bariatric Surgery

Abstract: Hypertrophic remodeling of white adipose tissues is associated with overexposure of lean organs to circulating triglycerides (TGs) and nonesterified fatty acids (NEFAs), ultimately leading to insulin resistance. Bariatric surgery promotes type 2 diabetes (T2D) remission through a succession of weight loss-dependent and -independent mechanisms. However, the longitudinal contribution of adipocyte size reduction and fatty acid metabolic handling remain unknown. Here we show that severely obese participants with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…However, adaptation of WAT TG/fatty acid cycling can reach impressive levels in humans. For example, using stable isotope tracer methodology in morbidly obese subjects before and 3 days, 3 months and 1 year after they underwent bariatric surgery, we showed that WAT NEFA production rate and storage capacity can be sustained at the same level despite a more than 3-fold reduction in adipose tissue mass ( 229 ), likely resulting in much enhanced energy expenditure per adipose tissue mass. Whether such WAT adaptations may contribute to chronic shift of total body energy balance remains to be tested.…”
Section: Is There a Contribution Of Wat Browning To Thermogenesis Andmentioning
confidence: 96%
“…However, adaptation of WAT TG/fatty acid cycling can reach impressive levels in humans. For example, using stable isotope tracer methodology in morbidly obese subjects before and 3 days, 3 months and 1 year after they underwent bariatric surgery, we showed that WAT NEFA production rate and storage capacity can be sustained at the same level despite a more than 3-fold reduction in adipose tissue mass ( 229 ), likely resulting in much enhanced energy expenditure per adipose tissue mass. Whether such WAT adaptations may contribute to chronic shift of total body energy balance remains to be tested.…”
Section: Is There a Contribution Of Wat Browning To Thermogenesis Andmentioning
confidence: 96%
“…Putative mechanisms have been hypothesized to explain the observed links between acylcarnitines, obesity, and diabetes [ 43 ]. Bariatric surgery has been associated with improved type 2 diabetes and major metabolic alterations, including fatty acid metabolism [ 43 , 44 ]. Medium- and long-chain fatty acids are transported as acylcarnitines across mitochondrial membranes for β-oxidation [ 6 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medium- and long-chain fatty acids are transported as acylcarnitines across mitochondrial membranes for β-oxidation [ 6 , 45 ]. Dodecanoylcarnitine and other acylcarnitines have a key role in fatty acid β-oxidation and have been hypothesized to indicate metabolic flexibility [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uncarboxylated osteocalcin ELISA. A sandwich enzyme-linked immunosorbent assay (ELISA) recognizing human ucOCN was established in collaboration with BioLegend Inc. using the 8H4 (anti-C-terminal) as a capture antibody and biotinylated 4B6 (anti-ucOCN [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] as the detection antibody (Cat. No.…”
Section: Methodsmentioning
confidence: 99%